2020
DOI: 10.3390/microorganisms8101577
|View full text |Cite
|
Sign up to set email alerts
|

Legacy Effects Overshadow Tree Diversity Effects on Soil Fungal Communities in Oil Palm-Enrichment Plantations

Abstract: Financially profitable large-scale cultivation of oil palm monocultures in previously diverse tropical rain forest areas constitutes a major ecological crisis today. Not only is a large proportion of the aboveground diversity lost, but the belowground soil microbiome, which is important for the sustainability of soil function, is massively altered. Intermixing oil palms with native tree species promotes vegetation biodiversity and stand structural complexity in plantations, but the impact on soil fungi remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 102 publications
1
15
0
Order By: Relevance
“…Here, we show that soil and root mineral nutrients were unaffected in the initial phase, one year after the start of the experimental treatments. This result agrees with other short-term studies, where management was stopped or reduced [51][52][53] and might have been expected because it is well known that agricultural soil usage has long-lasting legacy effects [54,55]. For example, recovery of N cycling takes almost a decade [56,57].…”
Section: Reduced Management Intensity Does Not Affect Root and Soil Chemistry Or Diversity Of Root-associated Phylasupporting
confidence: 91%
See 1 more Smart Citation
“…Here, we show that soil and root mineral nutrients were unaffected in the initial phase, one year after the start of the experimental treatments. This result agrees with other short-term studies, where management was stopped or reduced [51][52][53] and might have been expected because it is well known that agricultural soil usage has long-lasting legacy effects [54,55]. For example, recovery of N cycling takes almost a decade [56,57].…”
Section: Reduced Management Intensity Does Not Affect Root and Soil Chemistry Or Diversity Of Root-associated Phylasupporting
confidence: 91%
“…However, the opposite that recovery of AMF is one of the earliest effects in the root-associated fungal community is a novel result. This effect appears to be specific to roots since the presence of AMF in soil was unaffected in plots of oil palm plantations after discontinuing fertilization [54]. The observed recovery in AMF abundance has the potential for shifts in ecosystem functions since mycorrhizal fungi play a prominent role in plant nutrition and increase plant protection from pathogens [64,65].…”
Section: Fungal Guilds Show Differentiated Patterns To Reduced Fertilizer Application and Weedingmentioning
confidence: 94%
“…Development of next generation sequencing approaches has provided opportunities for culture-independent analysis of microbiomes for fine-level resolution of the diversity and composition of plant-associated microbiomes, characterization of the factors which shape community composition, and to reveal microbial interactions which affect plant health (Hilton et al, 2021). Several studies have used culture-independent approaches to investigate how plantation management (Ballauff et al, 2020) and the conversion of native forest to oil palm cultivation impacts the soil microbiome. Soil bacterial and fungal communities are impacted by oil palm cultivation (Lee-Cruz et al, 2013;Tripathi et al, 2016), including reduced abundance of ectomycorrhizal fungal associates of dipterocarp trees (McGuire et al, 2015), and increased abundance of AMF (Krashevska et al, 2015;Sahner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In soils of south-east Asian forest conversion systems (Borneo, Sumatra, Malaysia) massive shifts in whole fungal community composition were found but the relative abundance of Glomeromycota appeared to be little affected (Kerfahi et al, 2014;McGuire et al, 2015;Brinkmann et al, 2019). For example, McGuire et al (2015) found an overall decrease in fungal species richness (-30%) in plantation soil but a higher abundance of Glomerales in soils of oil palms than in primary or regeneration forests, while other studies using similar fungal amplicon-based sequencing techniques found no clear effects on AMF abundances (Kerfahi et al, 2014;Brinkmann et al, 2019;Ballauff et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…For example, McGuire et al. (2015) found an overall decrease in fungal species richness (-30%) in plantation soil but a higher abundance of Glomerales in soils of oil palms than in primary or regeneration forests, while other studies using similar fungal amplicon-based sequencing techniques found no clear effects on AMF abundances ( Kerfahi et al., 2014 ; Brinkmann et al., 2019 ; Ballauff et al., 2020 ).…”
Section: Discussionmentioning
confidence: 90%